Implementation of augmented reality-based digital citizenship learning to improve students' civic communication competence in higher education - Dini Nur Fadhillah; Cevi Mochamad Taufik; Nurul Febrianti; Suhaeri Suhaeri; Syurya Muhammad Nur (Universitas Negeri Yogyakarta, 2026)
Civic education is not limited to contemporary learning through traditional methods. Students are encouraged to actively participate through dialogue, collaboration, contribution, and discussion. Thus, the resulting discussions can stimulate their critical thinking regarding social issues. This study aims to analyse the implementation of augmented reality-based digital citizenship learning to improve the civic communication competence of higher education students. This study uses a qualitative case study approach. The participants in this study were 15 students from communication studies who took civic education courses. In-depth interviews were conducted using semi-structured techniques to collect data. The results of this study indicate that the use of augmented reality in civic education courses can help students identify forms of digital citizenship. Students can practise their civic communication competence through the DC-AR application. In addition, students can use the DC-AR application independently through their smartphones. Thus, the DC-AR application can be an alternative digital citizenship learning technology that can minimise the spread of hoaxes. Students are also encouraged to practise their social and cultural literacy skills through civic communication practices. This study concludes that civic education is not limited to theoretical elements. In higher education, civic education can be integrated with technology and communication science. Students not only understand digital citizenship but are also able to implement it through the DC-AR application by practising communication. The DC-AR application can also instil citizenship communication competencies in students as a strategy to improve the quality of human resources through education.